(untitled) (Modern education and development, 2025)
Alexander Arkadyevich Faynberg (1939–2009) was a poet, translator, and screenwriter whose work played a crucial role in connecting Russian and Uzbek literary traditions. This paper examines his contributions to poetry, his role in translating Uzbek literary masterpieces, and the stylistic characteristics that define his verse. Through an analysis of his major works, themes, and linguistic choices, this study highlights his influence on both Soviet and post-Soviet literature. Faynberg’s ability to blend cultural elements into his poetry makes him an essential figure in the study of intercultural literary exchange.